Eyewitness views : making history in eighteenth-century Europe. - Kerber, Peter Björn; J. Paul Getty Museum (Los Angeles : J. Paul Getty Museum, 2017)
"Accompanies an exhibition at the J. Paul Getty Museum in Los Angeles, the Minneapolis Institute of Arts, and the Cleveland Museum of Art and provides a comprehensive study of eighteenth-century view paintings that depict historical events"--
boek
Keywords: Narrative painting, European -- 18th century -- Exhibitions; Europe -- In art -- Exhibitions; History in art -- Exhibitions